Trends in Telestroke Care Delivery: A 15-Year Experience of an Academic Hub and Its Network of Spokes. Issue 3 (March 2020) - Sharma, Richa; Zachrison, Kori S.; Viswanathan, Anand; Matiello, Marcelo; Estrada, Juan; Anderson, Christopher D.; Etherton, Mark; Silverman, Scott; Rost, Natalia S.; Feske, Steven K.; Schwamm, Lee H.
Abstract : Background: Telestroke provides access to vascular neurology expertise for hospitals lacking stroke coverage, and its use has risen rapidly in the past decade. We aim to characterize consultations, spoke behavior, and the relationship between spoke telestroke utilization (number of telestroke consults per year) and spoke alteplase treatment metrics in an academic telestroke network. Methods and Results: We analyzed prospectively collected data on all telestroke consults from 2003 to 2018. Trends in network performance and spoke characteristics were analyzed using generalized estimating equations and Kendall τβ nonparametric tests as appropriate. Unadjusted and adjusted linear regression models determined associations between telestroke utilization and treatment metrics. The network included 2 hubs and 43 spokes with 12 803 consults performed during the study period. Network growth overall was +1.8 spokes per year, and median duration of spoke participation was 7.9 years. The numbers of consults and alteplase-treated patients increased annually, even after adjusting for the number of spokes in the network ( P <0.01 for both). Although times from last seen well to spoke emergency department arrival and to consult request increased, door-to-needle time, time from teleconsult request to callback, and time from teleconsult to alteplase administration all decreased (all P <0.01). With time, the network included more spokes without a Primary Stroke Center designation. In adjusted analyses, for every 10 telestroke consults requested by a spoke, the spoke door-to-needle decreased by 1.8 minutes ( P =0.02), number of patients treated with alteplase was an additional 1.7 ( P <0.01), and the percent of eligible patients treated with alteplase increased by 8% ( P =0.03). Conclusions: Telestroke network size and utilization increased over time. Increased use of teleconsults was associated with increased and timely use of alteplase. Over time, the delivery of timely emergency care has improved significantly among emergency departments participating in this telestroke network. Replication of these findings in other networks is warranted. Abstract : Supplemental Digital Content is available in the text.